Synthesis and Characterization of Polyaniline Nanoparticle by Inverse Micelle Microemulsion Method - Nuraini Uswatun Chasana; Siti Mariyah Ulfa; Masruri MASRURI (Chemistry Department, The University of Brawijaya, 2017)
Polyaniline (PANI) is a conductive polymer and potential for application in the electronic device manufacturing. This paper discloses a recent strategy in synthesis polyaniline nanoparticle (NP-PANI) using inverse micelle (IM) microemulsion method, and also characterization of the provided products. The synthesis step was conducted by mixing of aniline as a polymer precursor with PEG 400, n-hexane, n-butanol, ammonium persulfate and hydrochloric acid in three different reaction times, i.e. for 2, 6, and 12 hours at 26 oC. NP-PANI was afforded as a brown powder in 2.87%, 1.97% and 2.30% yield for NP-PANI-IM-2, NP-PANI-IM-6 and NP-PANI-IM-12. The characteristic on ultra violet-visible and infrared spectra exhibited NP-PANI was formed as an emeraldine salt oligomer. Moreover, their morphology was observed through scanning electron microscopy (SEM) and showed a different range of nanoparticle size, i.e. 50-62, 68-72 and 58-62 nm for NP-PANI-IM-2, NP-PANI-IM-6 and NP-PANI-IM-12, respectively. These products open the potency application in material science.